PENGARUH POTENSI AKADEMIK, EFIKASI DIRI DAN KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA - Ernawati Ernawati; Ilhamuddin Ilhamuddin (SIGMA: JURNAL PENDIDIKAN MATEMATIKA, 2022)
This type of research was ex-post facto research. The population in this study were all students of class XI of SMK Negeri 2 Makassar while the sample in this study were XI TKJ 1 and XI TKJ 2, totaling 65 students. The sampling technique used cluster random sampling. Data analysis techniques using questionnaires and tests. Data analysis techniques used descriptive statiscal analysis and inferential statistic analysis techniques. The results of this study indicate that (1) Partially, the academic potential variable significantly influences the learning outcomes of students of class XI SMK Negeri 2 Makassar of 17.6%. (2) Partially self-efficacy variables significantly influence the mathematics learning outcomes of class XI students of SMK Negeri 2 Makassar by 43.4%. (3) Partially the learning independence variable has a significant effect on the learning outcomes of Grade XI students of SMK Negeri 2 Makassar by 78.8%. (4) Simultaneously the variables of academic potential, self-efficacy and learning independence significantly influence the learning outcomes of students of class XI in SMK Negeri 2 Makassar with a coefficient of determination R2 = 0.817 which means that the academic potential, self-efficacy and learning independence gave an effect of 81.7% on the mathematics learning outcomes of students of class XI of SMK Negeri 2 Makassar and the remaining 18.3% is influenced by other factors